Marxism and literary criticism - Eagleton, Terry 1943- (Berkeley, California University of California Press, 1976)
Explores the growth of Marxist criticism in modern literary circles and demonstrates the role Marxism can play in creating a link between literature and historical conditions. Details major issues presented by this method of criticism and considers the work of such individuals as Plekhanov, Trotsky, Lenin, and Goldmann.
1. Literature and history: Marx, Engels and criticism -- Base and superstructure -- Literature and superstructure -- 2. Form and content: history and form -- Lukacs and literary form -- Goldmann and genetic structuralism -- Pierre Macherey and 'decentred' form -- 3. The writer and commitment: Art and the proletariat -- Marx, Engels and commitment -- The reflectionist theory -- 4. The author as producer: Art as production -- Walter Benjamin -- Bertolt Brecht and 'epic' theatre -- Form and production -- Realism or modernism? -- Consciousness and production.
Includes bibliographical references (pages [84]-87) and index.
Keywords: Marxist criticism; Communism and literature